CHET TILLINI O'RGANISHNING AHAMIYATI (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Speaking a foreign language has never been more important in our increasingly globalized society. Learning a second language provides access to a wealth of experiences and opportunities that monolingual people might otherwise pass up, whether for personal development, career advancement, or cultural enrichment. This article highlights the value of learning a foreign language in today's global society and examines its many advantages.